Optimized clustering method for spectral reflectance recovery - Xiong, Yifan; Wu, Guangyuan; Li, Xiaozhou; Wang, Xin (Frontiers in Psychology, 2022)
An optimized method based on dynamic partitional clustering was proposed for spectral reflectance recovery from camera response values. The proposed method produces dynamic clustering subspaces using a combination of dynamic and static clustering, which determines each testing sample as a priori clustering center to obtain the clustering subspace by competition. The Euclidean distance weighted and polynomial expansion models in the clustering subspace were adaptively applied to improve the spectral recovery accuracy. The experimental results demonstrate that the proposed method outperforms existing methods in spectral and colorimetric accuracy and presents the effectiveness and robustness of spectral recovery accuracy under different color spaces.